Effect of Unsaturated to Saturated Fatty Acids Ratio of Supplemental Fat in the Diet with or without L-Carnitine on Performance of Broiler Chicken - Swarna, Ch. Leela; Rao, S.V. Rama; Srinivas, Gurram; Reddy, V. Ravinder (Indian Journal of Animal Nutrition, 2018)
The present trial was conducted to study the effect of ratio of unsaturated to saturated fatty acids with or without L-carnitine supplementation on the performance male broiler chicks. A total of 320 day old male broiler chicks were randomly divided into 8 treatments with eight replicate and five birds each. T1, T2, T3 and T4 diets were formulated to contain ratio of UFA: SFA fatty acids as 60: 40, 65: 35, 70: 30 and 75: 25, respectively. Diets T5, T6, T7 and T8 were formulated to contain same ratio of fatty acids to that of T1 to T4 but with supplementation of L-carnitine at 100 mg/kg diet level. Before the feed formulation, the lipid profile of the tallow and crude soybean oil were analyzed. The unsaturated fatty acids (UFA) : saturated fatty acids (SFA) ratio were found to be 5.37 and 0.77, respectively for crude soybean oil and tallow. The results indicated that 70: 30 ratio without L-carnitine had significantly (P<0.05) higher weight gain during starter, finisher and overall period compared to other ratios. However, carnitine supplementation to these ratios did not have significant effect on weight gain during the finisher and the overall period. Significantly (P<0.05) lowest feed intake was noticed at 75: 25 ratio with L-carnitine supplementation. The FCR was better (P<0.05) at 60: 40 ratio diets without carnitine supplementation compared to others. The interaction effect was significant (P<0.05) only during starter phase.